A HIF-1α inhibitor combined with palmitic acid and L-carnitine treatment can prevent the fat metabolic reprogramming under hypoxia and induce apoptosis in hepatocellular carcinoma cells - Shohei Matsufuji; Yoshihiko Kitajima; Kazuki Higure; Naoya Kimura; Sachiko Maeda; Kohei Yamada; Kotaro Ito; Tomokazu Tanaka; Keita Kai; Hirokazu Noshiro (Cancer & Metabolism, 2023)
Abstract Background A hypoxic environment often persists within solid tumors, including hepatocellular carcinoma (HCC). Hypoxia-inducible factor-1α (HIF-1α) can accelerate cancer malignancy by inducing hypoxia-dependent expression of various genes. Tumor hypoxia can also induce metabolic reprogramming of fatty acid (FA) metabolism, through which HIF-1α plays an essential role in diminishing fatty acid β-oxidation (FAO) in hypoxic cancer cells. Methods We aimed to investigate potential new drug therapy options for targeting hypoxic cancer cells within HCC tumors, specifically through combining HIF-1α inhibition with palmitic acid (PA) + L-carnitine (LC) treatment to effectively induce apoptosis in hypoxic HCC cells. To test this hypothesis, in vitro and in vivo studies were performed. Results We first demonstrated that hypoxia-dependent apoptosis was induced by an overload of PA in two HCC cell lines (HepG2 and Hep3B) via excessive production of reactive oxygen species (ROS). Moreover, this observed PA-induced apoptosis was enhanced by HIF-1α knockdown (KD) in these cells under hypoxia. In addition, the combination of PA with FAO activator LC increased FAO activity and led to stronger cell death than PA alone in hypoxic HIF-1α KD cells, specifically through further ROS generation. To clarify the mechanism of hypoxia-induced FA metabolism reprogramming, expression levels of the genes encoding FAO enzymes CPT1A, ACSL1, MCAD, and LCAD, FA transporter CD36, and FA esterification enzymes DGAT and APGAT were analyzed using HIF-1α KD and scramble control (SC) cells. The results suggested that HIF-1α could repress mRNA expression of the FAO-related enzymes and CD36, while it upregulated FA esterification gene expression. This suggested a central role for HIF-1α in hypoxia-induced reprogramming of FA metabolism in HCC cells. Using a nude mouse model, PA administration was found to induce apoptosis from ROS overproduction in HIF-1α KD tumors compared with SC tumors. Additional LC treatment synergistically enhanced the PA-induced apoptosis in HIF-1α KD tumors. Finally, in vivo therapy composed of HIF-1α inhibitor YC-1 with PA + LC could induce ROS-mediated apoptosis in HepG2 tumors without significant toxicity. Conclusions A combination therapy of YC-1 with PA + LC may be a unique anti-tumor therapy for targeting hypoxic HCC cells, specifically by ROS overproduction leading to forced FAO activation.